2021
DOI: 10.1021/acs.nanolett.1c00757
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Spherical Superstructure of Carbon Nanosheets for Bifunctional Oxygen Reduction and Evolution Electrocatalysis

Abstract: The pyrolysis of metal–organic frameworks (MOFs) is an ingenious way to synthesize carbon-based materials with unique morphology for various applications including electrocatalysis. In this work, we reported a facile morphology regulation strategy for the synthesis of a spherical superstructure of MOF nanosheets. The use of metal hydroxide nanosheets on Zn particles as precursors/templates allowed MOFs with general polyhedron shape to form nanosheets and assemble into a spherical superstructure in the ligand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…4d), which is above the 181.8 mW cm À2 for Pt/C// RuO 2 as well as those of other recently reported metal catalysts, e.g., porous structure Fe/N-G-SAC (120 mW cm À2 ), 47 novel coreshell CuMo 2 ON@NG (176.3 mW cm À2 ), 48 dual-linkage 3D Mn/ Fe-HIB-MOF (195 mW cm À2 ) (Table S3 †), 49 dual-phase CNT@SAC-Co/NCP (172 mW cm À2 ), 50 yolk-shell hollow spheres N-CoS2 YSSs (81 mW cm À2 ), 51 3D-structured CoFe@NC/ CC (154.2 mW cm À2 ), 52 and nanosheets FeCoNi/HCS (156.7 mW cm À2 ). 53 It is worth noting that the CoFe@NOC air battery cathode has a specic capacity of 829.5 mA h g Zn À1 at 5 mA cm À2 (Fig. 4e), higher than the specic capacity of Pt/C//RuO 2 (791.1 mA h g Zn À1 ).…”
Section: Zn-air Battery Characterizationmentioning
confidence: 87%
“…4d), which is above the 181.8 mW cm À2 for Pt/C// RuO 2 as well as those of other recently reported metal catalysts, e.g., porous structure Fe/N-G-SAC (120 mW cm À2 ), 47 novel coreshell CuMo 2 ON@NG (176.3 mW cm À2 ), 48 dual-linkage 3D Mn/ Fe-HIB-MOF (195 mW cm À2 ) (Table S3 †), 49 dual-phase CNT@SAC-Co/NCP (172 mW cm À2 ), 50 yolk-shell hollow spheres N-CoS2 YSSs (81 mW cm À2 ), 51 3D-structured CoFe@NC/ CC (154.2 mW cm À2 ), 52 and nanosheets FeCoNi/HCS (156.7 mW cm À2 ). 53 It is worth noting that the CoFe@NOC air battery cathode has a specic capacity of 829.5 mA h g Zn À1 at 5 mA cm À2 (Fig. 4e), higher than the specic capacity of Pt/C//RuO 2 (791.1 mA h g Zn À1 ).…”
Section: Zn-air Battery Characterizationmentioning
confidence: 87%
“…[12] Metal-organic frameworks (MOFs), which possess diverse structures and chemical compositions, have attracted significant attention as one of the best template candidates to fabricate hollow structures. [13] Also, some trials have indicated that MOFs can be converted into LDHs under appropriate treatments. [11d] For example, Zhang and his coworkers [14] constructed NiÀ Fe LDH nanocages with tunable shells via a facile one-pot self-templating method, which exhibited appealing electrocatalytic activity for OER in alkaline electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the SS-CNRs possess an ultrahigh BET surface area (S BET = 1406 m 2 g −1 ) compared with irregular CNPs (S BET = 1199 m 2 g −1 ), which would contribute to exposing more active sites and accelerating the mass transport. 34,35 Surprisingly, the specific surface areas of the CNRs (S BET = 2565 m 2 g −1 ) are much larger than those of the SS-CNRs, however, whose catalytic activity was proven to be far smaller than that of the SS-CNRs by subsequent electrochemical tests. It probably comes down to the void-confinement effects and the reconfiguration of the internal electronic structure caused by the special morphology.…”
Section: ■ Results and Discussionmentioning
confidence: 98%